2020
DOI: 10.1016/j.lfs.2020.118308
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy markers as mediators of lung injury-implication for therapeutic intervention

Abstract: Lung injury is characterized by inflammatory processes demonstrated as loss of function of the pulmonary capillary endothelial and alveolar epithelial cells. Autophagy is an intracellular digestion system that work as an inducible adaptive response to lung injury which is a resultant of exposure to various stress agents like hypoxia, ischemia-reperfusion and xenobiotics which may be manifested as acute lung injury (ALI), acute respiratory distress syndrome (ARDS), chronic lung injury (CLI), bronchopulmonary dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 181 publications
(232 reference statements)
3
38
0
Order By: Relevance
“…Acute lung injury (ALI) and its worse form, acute respiratory distress syndrome (ARDS) consist of a set of pathological lung modifications that occur from pulmonary destructive events, such as pneumonia, sepsis, pulmonary trauma, viral infections and various other situations or diseases (116)(117)(118). Such phenomena deteriorate the vascular endothelium and the alveolar epithelium (119) resulting in loss of function of the corresponding cells due to excessive inflammation, hypoxemia and eventually respiratory failure (120,121). Both ALI and ARDS, due to the severe nature of their manifestations, are characterized by high mortality rates, despite the available treatment options that aim to optimize the diseases' outcome (116,122).…”
Section: Acute Lung Injury Acute Respiratory Distress Syndrome and Ace I/d Polymorphismmentioning
confidence: 99%
“…Acute lung injury (ALI) and its worse form, acute respiratory distress syndrome (ARDS) consist of a set of pathological lung modifications that occur from pulmonary destructive events, such as pneumonia, sepsis, pulmonary trauma, viral infections and various other situations or diseases (116)(117)(118). Such phenomena deteriorate the vascular endothelium and the alveolar epithelium (119) resulting in loss of function of the corresponding cells due to excessive inflammation, hypoxemia and eventually respiratory failure (120,121). Both ALI and ARDS, due to the severe nature of their manifestations, are characterized by high mortality rates, despite the available treatment options that aim to optimize the diseases' outcome (116,122).…”
Section: Acute Lung Injury Acute Respiratory Distress Syndrome and Ace I/d Polymorphismmentioning
confidence: 99%
“…The effect is obvious when CA is 8 μ g/ml. At the same time, the autophagy protein LC3B [ 30 ] was detected, and the results showed it to be significantly inhibited when CA was 8 μ g/ml. Autophagy has a close relationship with anoxic microenvironment [ 31 ], but the further relationship requires further study in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…SQSTM1 is known as an autophagy protein that is involved in ubiquitin-proteasome and autophagy-lysosome degradation processes [25]. Liu Y et al revealed that the relationship between Na, K-ATPase and autophagy-lysosome pathway requires the involvement of α1 subunit, and Na, K-ATPase α1 and AMPK may act as the "on" and "off" switch of autophagy pathway [26].…”
Section: Discussionmentioning
confidence: 99%